Effect of five-element cupping therapy on postoperative wound pain of patients with mixed hemorrhoids (五行能量罐治疗混合痔术后伤口疼痛效果观察) - WEI Yongchun (魏永春); QIN Shasha (秦沙沙); ZHANG Kaiye (张凯烨); WANG Yali (王亚丽); DONG Yuxia (董玉霞); E Haiyan (鄂海燕); TANG Ling (唐玲) (中西医结合护理)
Objective To investigate the effect of Traditional Chinese Medicine (TCM) five-element cupping therapy on postoperative wound pain of patients undergoing Milligan-Morgan surgery for mixed hemorrhoids of damp-heat type. Methods Totally 60 patients undergoing Milligan-Morgan surgery for mixed hemorrhoids of damp-heat type were randomly divided into the observation group and control group, with 30 cases in each group. Anti-infection, hemostasis and other symptomatic treatment were carried out after surgery. The control group received routine wound cleansing and dressing change, and the observation group received TCM five-element cupping therapy on the basis of routine care. The Visual Analogue Scale (VAS) was used to assess the wound pain degree at 24 h、48 h、72 h after treatment. Results The VAS score in the treatment group was significantly lower than that in the control group at 24 h、48 h and 72 h after treatment, respectively (P＜0. 01). Conclusion The TCM five-element cupping therapy is effective to relieve the postoperative pain of patients with mixed hemorrhoids. It is an easy-to-operate and safe technique of TCM nursing, which is worthy of promoting in pain control after surgical treatment for anorectal diseases. (目的 观察五行能量罐治疗混合痔(湿热下注型)术后伤口疼痛的效果。方法 选取2021年5月—12月行手术治疗的混合痔(湿热下注型)患者共60例, 采用随机数字表法分为观察组和对照组, 各30例。两组患者均在麻醉下行混合痔外剥内扎术, 术后常规给予抗感染、止血等对症治疗。对照组接受术后常规换药护理, 观察组在对照组基础上增加五行能量罐中医护理干预。采用疼痛视觉模拟评分(VAS)分别对治疗后24 h、48 h、72 h伤口疼痛程度进行评价。结果 观察组拔罐治疗后24 h、48 h、72 h的疼痛评分低于对照组, 差异有统计学意义(P＜0. 01)。结论 五行能量罐中医护理干预能减轻混合痔术后患者伤口疼痛程度, 且操作简便, 患者依从性好, 可以广泛应用于包含混合痔在内的多种肛肠疾病术后疼痛护理中。)